Transport of Solutes in Soil: Basic Features of Front Retardation - Bolt, G. H. (Water science and technology, 1985)
Application of the integral conservation equation to a moving concentration front provides the basis for calculation of its mean rate of movement. Doing so shows that the simultaneous presence of different adsorbates exhibiting differing adsorption isotherms leads to the formation of a corresponding number of concentration fronts separated by a transition region. It is shown that in this region concentration levels in excess of those occurring in both the feed solution and in the initial solution phase are characteristic. A similar reasoning applies to the situation where an incoming solute in the mobile solution phase is subject to the formation of a precipitate with an ion driven off the solid phase by an also incoming competitor for adsorption sites on the solid phase. Then again excessive concentration levels are shown to arise occasionally in the transition zone between the precipitation and dissolution fronts. Finally the effect of a delayed equilibration between the mobile and an immobile (adsorbing) phase is discussed briefly.